Problem Based Learning Model to Improve Understanding of the Material on Faith in the Books of Allah in Class VIII MTsN 7 Madiun - Muhammad Bahrul Mu'in (Islamic Journal of Teaching and Learning, 2025)
This study aims to improve students' understanding of the topic Faith in the Scriptures of Allah through the implementation of the Problem-Based Learning (PBL) model in Grade VIII of MTsN 7 Madiun, Indonesia. The research employed Classroom Action Research (CAR) with two cycles, involving 31 students. Data were collected through observation, tests, and documentation, and analyzed using descriptive quantitative and qualitative approaches. The results indicate an increase in students' understanding: the average score rose from 68.12 (pre-cycle) to 74.35 (cycle I) and 82.58 (cycle II). Learning mastery also improved from 32.25% to 87.09%. Furthermore, students' activeness, quality of discussion, and ability to relate the material to real-life contexts showed significant progress. The research demonstrates practical implications for Islamic education methodology, showing that contextual problem-solving approaches can effectively bridge theoretical religious concepts with contemporary challenges faced by students. It is concluded that PBL is effective in teaching Akidah Akhlak, particularly on the topic of Faith in the Scriptures of Allah, as it enhances understanding, engagement, and the application of Islamic values in daily life.